Beyond a Decade of Water Justice: Review, Directions, and Pathways to Achieve “Water for All” - Fanaian, Safa; Manero, A.; Nguyen, N.; Grafton, R. Q. (Wiley, 2025)
Water justice is increasingly recognized as central to achieving Sustainable Development Goal 6 (SDG 6), which seeks universal access to safe water and sanitation. Yet persistent injustices in water access, allocation, governance, and participation continue to undermine this goal. Despite growing global attention to and applications of “water justice,” a critical disconnect between understanding and practice highlights the need for a formal review and synthesis of just, equitable, and sustainable water management and governance. In response, we provide a comprehensive review of water justice scholarship published between 2012 and 2023. We systematically review and synthesize insights from 470 peer-reviewed studies to examine the evolution of water justice concepts, map their alignment with SDG sub-goals over time, and inventory proposed solutions. Our findings reveal a shift in the literature from an emphasis on distribution and procedural justice to a more recent focus on decolonial, socio-ecological, and pluralistic approaches to water justice. Our review highlights persistent barriers to water justice, including entrenched power asymmetries, institutional capture, and policy misalignment, while also identifying emerging responses focused on hybrid governance models, co-production processes, and justice-oriented social movements. We conclude that further advances in water justice research and practices require greater consideration of structural inequalities, reappraisal of water governance approaches, comparisons of alternative evidence-based, and context-specific actions, and an analysis of transformative responses to injustices.